Antennas and Propagation Conference 2019 (APC-2019) 2019
DOI: 10.1049/cp.2019.0690
|View full text |Cite
|
Sign up to set email alerts
|

8×8 MIMO Antenna System with Coupled-Fed Elements For 5G Handsets

Abstract: In this paper, a new design of multiple-input/multiple-output (MIMO) antenna is proposed for 3.6 GHz fifth generation (5G) mobile communications. The proposed design contains four pairs of compact microstrip-fed dual-polarized antennas that are symmetrically placed at the four corners of the smartphone printed circuit board (PCB). Each antenna pair consists of a square loop radiation patch and a square defected ground structure (DGS). The loop radiators are fed by two independently coupled Tshaped microstrip f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…7. Therefore, it can be concluded that the closest distance between antenna elements and the user-head leads to a maximum SAR value, and the furthest distance leads to a minimum SAR value [44,45]. Compared with Figure 8, the maximum reduction of antenna gain is observed for the elements closely spaced with the user's head and hand.…”
Section: User Impacts On the Performance Of The Cpw-fed Smartphone Anmentioning
confidence: 78%
See 1 more Smart Citation
“…7. Therefore, it can be concluded that the closest distance between antenna elements and the user-head leads to a maximum SAR value, and the furthest distance leads to a minimum SAR value [44,45]. Compared with Figure 8, the maximum reduction of antenna gain is observed for the elements closely spaced with the user's head and hand.…”
Section: User Impacts On the Performance Of The Cpw-fed Smartphone Anmentioning
confidence: 78%
“…7. Therefore, it can be concluded that the closest distance between antenna elements and the user-head leads to a maximum SAR value, and the furthest distance leads to a minimum SAR value [44,45]. The Snn (S11~S88) and efficiency characteristics of the CPW-fed MIMO smartphone antenna in the presence of battery, speaker, camera, USB connector and LCD screen are investigated and illustrated in Figure 20.…”
Section: User Impacts On the Performance Of The Cpw-fed Smartphone Anmentioning
confidence: 99%
“…2 × 2 MIMO systems are successfully employed for 4G mobile networks and the massive MIMO system with a large number of antenna elements is expected to be applied for 5G communications [6][7][8]. Recently, several MIMO antenna designs have been introduced for 5G cellular systems [9][10][11][12][13][14][15]. However, all these mobile-phone antenna designs either exhibit single-band operation frequency or use a few antenna elements with large sizes which could occupy a huge space of smartphone mainboard.…”
Section: Introductionmentioning
confidence: 99%
“…of the petal arm), (c)x (width of the ring), and (d) h x (thickness of the substrate). As can be observed, the antenna frequency response is very flexible to be tuned to lower or upper frequencies [21,22]. Its impedance matching can also be affected by changing the parameter values.…”
Section: Introductionmentioning
confidence: 99%